Fraud, corruption and sport - Brooks, Graham, 1964- (Palgrave Macmillan, 2020)
Sport plays a collective social, political and cultural role around the world. In recent years, however, it has become associated with stories of corruption including gambling, consumption of illegal substances and institutional vote rigging. This book examines the level, depth and range of fraud and corruption in sport and the methods used to counteract and prevent fraud and corruption which damages the integrity of sport.Brooks, Aleem and Button argue that sport is often downplayed and defended as 'different' from other businesses. This book demonstrates that sport encounters the same types of fraud and corruption as business everywhere, and those specific to it such as match fixing, point shaving associated with vested gambling interests and tanking to secure better players in the future. Fraud, Corruption and Sport analyses a diverse range of cases internationally from across the sporting world including football, cricket, horse racing, basketball, baseball and boxing.This book presents a new perspective on the security of sport appealing to students, academics, practitioners and sporting enthusiasts alike"--|cProvided by publisher.Machine generated contents note: -- 1. Introduction -- PART I: FRAUD, CORRUPTION AND SPORT IN CONTEXT -- 2. Defining Fraud and Corruption in Sport -- 3. Defining Fraud -- 4. Defining Corruption -- 5. Developing a Typology of Fraud and Corruption in Sport -- 6. The Art of Bending and Breaking the Rules: A Continuum of Corruption -- 7. A Culture of Corruption: a Systemic Problem or Protecting Vested Interests? -- 8. Gambling: A Cause of Fraud and Corruption in Sport? -- 9. The Extent of Fraud and Corruption in Sport -- 10. The Problem in Measuring Fraud and Corruption in Sport -- 11. Surveys and Estimates of Fraud and Corruption in Sport -- 12. The Limitation of Surveys of Fraud and Corruption Data -- 13. Gambling and Sport: Measuring 'Attempted' Fraud and Corruption? -- 14. Why do Those in Sport Commit Fraud? -- 15. Individual Athletes and Acts of Fraud and Corruption -- 16. Sporting Institutions and Acts of Fraud and Corruption -- 17. Internet Fraud, Corruption and Sport -- 18. Money Laundering and Gambling Websites -- 19. Under Threat from 'Organised' Crime: Fraud, Corruption and Online Gambling Websites -- PART II: KEY BODIES: ENFORCEMENT AND GOVERNANCE -- 20. Fraud and Corruption in Football -- 21. Types of Fraud and Corruption in Football -- 22. Ticket Sales -- 23. Football Agents, Fees and Potential Tax Evasion -- 24. Match Fixing and its Association with Gambling -- 25. The Potential for Money Laundering and Lost Taxation from Football Clubs -- 26. Countering Fraud and Corruption in Football: A Structural Problem for Football Leagues -- 27. German Football: Broad Involvement, Limited Regulation and Incentives for Financial Window Dressing -- 28. The Structure of Italian Football: Creative Accounting in a Family Business? -- 29. Detecting, Exposing and Preventing Fraud and Corruption in Football -- 30. Fraud and Corruption in Cricket -- 31. Types of Fraud and Corruption in Cricket -- 32. Paying for Information -- 33. Match Fixing -- 34. Spot-fixing -- 35. Countering Fraud and Corruption in Cricket: The Role(s) of the ICC ACSU and National Boards -- 36. Detecting and Exposing Fraud and Corruption in Cricket: a Need for Special Investigators? -- 37. Fraud and Corruption in Horse Racing -- 38. Types of Fraud and Corruption in Horse Racing -- 39. Trading a Horse or Horse-trading? Buying a Horse at Auction -- 40. Auction Fraud in the United Kingdom and USA -- 41. Fixing Horse Races: Doping and Gambling in the Name of Profit? -- 42. Detecting, Exposing and Countering Fraud and Corruption in Horse Racing -- 43. Fraud and Corruption in Basketball -- 44. Types of Fraud and Corruption in Basketball -- 45. Point Shaving -- 46. Referee Bias -- 47. Tanking: Losing to Win? -- 48. Detecting, Countering and Exposing Fraud and Corruption in Basketball -- 49. Fraud and Corruption in Baseball -- 50. Types of Fraud and Corruption in Baseball -- 51. Match Fixing for Money: A Justification for Poor Pay and Restrictive Contracts? -- 52. Match Fixing for Glory: Little League Baseball (LLB) and State Corruption in Taiwan -- 53. Match Fixing for Organised Interests: Bribery, Threats and Intimidation -- 54. Detecting, Countering and Exposing Fraud and Corruption in Baseball: The Role(s) of the Major League Baseball (MLB) -- 55. Recourse to the Law: Getting MLB Attention? -- 56. Fraud and Corruption in Boxing -- 57. Types of Fraud and Corruption in Boxing -- 58. The Participants -- 59. Boxers -- 60. Managers -- 61. Promoters -- 62. Boxing Commissions -- 63. Sanctioning Organisations -- 64. Detecting, Exposing and Countering Fraud and Corruption in Boxing: The Evolution of Federal Regulation of Boxing -- 65. Preventing some Fraud and Corruption in Boxing: Improving Contracts, Developing a Database of Boxers and Employing Credible Referees and Judges -- 66. Overview and Final Reflections -- Bibliography.